A educação ambiental crítica na formação de professores de creche: contribuições do pensamento de Paulo Freire - Habyak, Roberta Candida (2023)
Currently, the majority of the world population lives in urban areas, having little concern with environmental issues. Thus, environmental issues seem to make more sense to the native peoples, riverside communities and environmentalists. Regarding the lack of contact and knowledge of most people in relation to this issue, the role that teachers play in building interactions between children and the environment as well as the assumption that critical environmental education contributes to the critical transformative education of nursery school professionals, this research proposes a dialogue between teacher education and critical environmental education, inspired by Paulo Freire's framework. The dialogue was built from the following questions: In the sense of a critical transformative educational practice, can the interactions with the environment - based on the reading of reality - cause changes? In a humanizing perspective, does the debate of critical environmental education concepts contribute to teacher education? The main objective of this research is to understand critical environmental education as an instrument for the development of critical transformative teachers. The object of the research was the training of nursery teachers who work in the city of Santo André-SP, with the following specific objectives: (1) to identify the presence of environmental education in the Political-Pedagogical Project of nursery schools and/or in the teachers’ practices; (2) to identify the conceptions of environmental education and the needs/expectations of teachers regarding teacher training that involve this theme; (3) supported by the Freirean pedagogy and critical environmental education, to draw up a proposal for teacher training in environmental education, based on the analysis of the teachers' educational needs. Regarding teacher education, the theoretical framework is based on Paulo Freire's ideas. To discuss critical environmental education, we focused on the studies of Carlos Frederico Loureiro, Mauro Guimarães and Philippe P. Layrargues. To answer the questions and build perspectives for teacher education and critical environmental education, this research has a qualitative approach. The procedures and instruments for data collection included: group discussion, interviews and a survey. Data analysis was based on the concepts presented in the Freirean Conceptual Plot, developed by Ana Maria Saul and Alexandre Saul. The analysis revealed: greater incidence of the pragmatic conception of environmental education in the pedagogical practices; that the critical aspect of environmental education needs to be widely debated; that the collective construction of the Political-Pedagogical Project is a possibility to integrate the educators to the reality of the school community and to develop collective projects; and that nursery schools need green areas that allow the contact of young children with nature. As a result, this research proposes the Freirean concepts of reading of reality, dialogue and participation as an orientation for the development of the training processes of critical transformative teachers. We hope that these reflections contribute to the pedagogical practice of critical environmental education in nursery schools and to the development of critical subjects